Apelin-13 Reverses Bupivacaine-Induced Cardiotoxicity via the Adenosine Monophosphate–Activated Protein Kinase Pathway. (17th August 2021) - Ye, Yingchao; Cai, Yaoyao; Xia, Erjie; Shi, Kejian; Jin, Zhousheng; Chen, Hongfei; Xia, Fangfang; Xia, Yun; Papadimos, Thomas J.; Xu, Xuzhong; Liu, Le; Wang, Quanguang
Abstract : BACKGROUND: Cardiotoxicity can be induced by the commonly used amide local anesthetic, bupivacaine. Bupivacaine can inhibit protein kinase B (AKT) phosphorylation and activated adenosine monophosphate–activated protein kinase alpha (AMPKα). It can decouple mitochondrial oxidative phosphorylation and enhance reactive oxygen species (ROS) production. Apelin enhances the phosphatidylinositol 3-kinase (PI3K)/AKT and AMPK/acetyl-CoA carboxylase (ACC) pathways, promotes the complete fatty acid oxidation in the heart, and reduces the release of ROS. In this study, we examined whether exogenous (Pyr1) apelin-13 could reverse bupivacaine-induced cardiotoxicity. METHODS: We used the bupivacaine-induced inhibition model in adult male Sprague Dawley (SD) rats (n = 48) and H9c2 cardiomyocyte cell cultures to explore the role of apelin-13 in the reversal of bupivacaine cardiotoxicity, and its possible mechanism of action. AMPKα, ACC, carnitine palmitoyl transferase (CPT), PI3K, AKT, superoxide dismutase 1 (SOD1), and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (p47-phox) were quantified. Changes in mitochondrial ultrastructure were examined, and mitochondrial DNA, cell viability, ROS release, oxygen consumption rate (OCR) were determined. RESULTS: Apelin-13 reduced bupivacaine-induced mitochondrial DNA lesions in SD rats ( P < .001), while increasing the expression of AMPKα ( P = .007) and PI3K ( P = .002). Furthermore, apelin-13 blocked bupivacaine-induced depolarization of the mitochondrial membrane potential ( P = .019) and the bupivacaine-induced increases in ROS ( P = .001). Also, the AMPK pathway was activated by bupivacaine as well as apelin-13 ( P = .002) in H9c2 cardiomyocytes. Additionally, the reduction in the PI3K expression by bupivacaine was mitigated by apelin-13 in H9c2 cardiomyocytes ( P = .001). While the aforementioned changes induced by bupivacaine were not abated by apelin-13 after pretreatment with AMPK inhibitor compound C; the bupivacaine-induced changes were still mitigated by apelin-13, even when pretreated with PI3K inhibitor-LY294002. CONCLUSIONS: Apelin-13 treatment reduced bupivacaine-induced oxidative stress, attenuated mitochondrial morphological changes and mitochondrial DNA damage, enhanced mitochondrial energy metabolism, and ultimately reversed bupivacaine-induced cardiotoxicity. Our results suggest a role for the AMPK in apelin-13 reversal of bupivacaine-induced cardiotoxicity.